Hydrophilic treatment for strong carbon nanotube fibers. (23rd April 2021) - Cheon, Jae Yeong; Ku, Nayoung; Jung, Yeonsu; Lee, Kyunbae; Kim, Taehoon
Abstract: The hydrophobic surface characteristics of carbon nanotube fibers (CNTFs) limit their usage in aqueous systems. Herein, we report a surface treatment method for preparing hydrophilic CNTFs by attaching a sulfonic acid group onto the surface of CNTF. The introduction of a sulfonic acid group was examined by x-ray photoelectron spectroscopy. The contact angle between the CNTF and water droplets decreased after a surface treatment to 22.9°, implying enhanced hydrophilicity. The nanostructure of the CNTF is rarely changed during surface treatment, so the surface characteristics can be controlled without losing the advantages of direct-spun CNTFs. Water infiltration was examined by measuring the electric double-layer capacitance of CNTFs. The capacitance of surface-treated CNTFs (140 μ F cm −1 ) was even higher than the as-prepared CNTFs (21 μ F cm −1 ), meaning that the interfacial area between CNTFs and water electrolytes significantly increased, and water can infiltrate effectively into the nanopores of CNTFs as a result of the surface treatment. The sulfonic acid group is more efficient than the carboxyl group in improving hydrophilicity and water infiltration. The surface treatment also enhances the specific strength of the CNTFs by 50%, which is beneficial for preparing CNTF-based devices. The hydrophilic CNTFs prepared in this work will be useful in preparing CNTF-possessing functional nanoparticles or in use in CNTFs for electrochemical devices.